Two Different Profiles for Packaging RNA inside Viruses - Tuyen, Tran Thanh; Khanh, Nguyen Van; Thuy, Nguyen Van; Quyen, Vu Van; Toan, Nguyen The (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: The problem of RNA genomes packaged inside spherical viruses is studied. The viral capsid is modeled as a hollowed sphere. The attraction between RNA molecules and the inner viral capsid is assumed to be non-specific and occurs at the inner capsid surface only. For small capsid attraction, it is found that monomer concentration of RNA molecules is maximal at the center of the capsid to maximize their configurational entropy. For stronger capsid attraction, RNA concentration peaks at some distance near the capsid. In the latter case, the competition between the branching of RNA secondary structure and its adsorption to the inner capsid results in the formation of a dense layer of RNA near capsid surface. The layer thickness is a slowly varying (logarithmic) function of the capsid inner radius. Consequently, for immediate strength of RNA-capsid interaction, the amount of RNA packaged inside a virus is proportional to the capsid area (or the number of proteins) instead of its volume. The numerical profiles describe reasonably well the experimentally observed RNA nucleotide concentration profiles of various viruses. Keywords: RNA viruses, RNA condensation, viral RNA packaging, RNA structure.